Description of the first species of Nemeritis Holmgren (Hymenoptera: Ichneumonidae: Campopleginae) from the Southern Hemisphere, with a key to the New World species - Araujo, Rodrigo O.; Giovanni, Filippo Di (Zootaxa, 2021)
Nemeritis Holmgren, 1860 is a moderately species-rich genus of Campopleginae (Hymenoptera: Ichneumonidae) which includes 42 valid species, occurring in the Western Palearctic, Eastern Palearctic, Nearctic, and Oriental regions. Herein, a new species from Chile, Nemeritis scaramozzinoi sp. nov., is described. This is the first description of a species of Nemeritis for the Southern Hemisphere. The key for the New World species of the genus and biogeographical remarks on the Chilean fauna of Darwin wasps are also provided.